1888 Utah Laws 166, ch. 50, § 19, pt. 31. - (:unkn) unknown (General Publisher, 1888)
To adopt such rules and regulations within their respective counties, except within municipal corporations, with regard to the keeping and storing of every kind of gun powder, [H]ercules powder, giant powder, or other combustible material, as the safety and protection of the lives and property of individuals may require.
--
Keywords: GUN POWDER STORAGE